To solve the equation \( 4x = 3(x + 5) - 15 \), we will start by simplifying the right side.
-
Expand the right side: \[ 3(x + 5) = 3x + 15 \] So, \[ 3(x + 5) - 15 = 3x + 15 - 15 = 3x \]
-
Now, we have the equation: \[ 4x = 3x \]
-
Next, we will subtract \( 3x \) from both sides: \[ 4x - 3x = 0 \] This simplifies to: \[ x = 0 \]
Now we check the conclusions:
- The equation \( 4x = 3(x + 5) - 15 \) simplifies to \( 4x = 3x \), which leads us to \( x = 0 \).
- This means there is one solution.
Thus, the answer is: The equation has one solution: x=0.